The Impact of Teacher Teaching in Developing Critical Thinking on Students' Critical Reading Ability - Munawaroh, Lavifatul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Researchers believe that awareness and monitoring of comprehension processes are very important for developing one's reading skills. One of the main issues in the world of education today is concern about students' ability to read critically and evaluate the material they read. This research aims to investigate the impact of teacher teaching in developing critical thinking on students' critical reading abilities. To achieve this goal, we selected 50 students from private high schools with an age range of 16-18 years as research participants. They were then divided into two groups, namely the experimental group and the control group, after being homogenized through the Nelson test. Next, the same content in the form of ten reading texts was taught to both groups, with the only difference that the experimental group received training in critical reading strategies such as annotating, asking questions, detailing, summarizing, and concluding, while the control group applied a general comprehension approach. The results of data analysis using an independent t-test show that teaching critical reading strategies has a significant impact on the development of students' critical reading skills, resulting in rejection of the null hypothesis. These findings can have relevant implications for the Impact of Teacher Teaching in Developing Critical Thinking on Students' Critical Reading Ability, promoting learning in authentic, interactive, and student-focused environments in their reading classes.